PENINGKATAN KESEJAHTERAAN LANSIA MELALUI PEMERIKSAAN KESEHATAN - Herrywati Tambunan; Nurhidayati; Siti Saleha (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2023)
The elderly is a human age group entering the final stages of life. From the health aspect, the elderly group experiences a decline in health status, both naturally and as a result of disease, and a special approach and efforts are needed for the elderly to improve the quality of health on an ongoing basis. The elderly should receive attention to their health, so that they are healthy and live long, are not dependent on the family, and can live independently, it is necessary to carry out regular health checks for the elderly. The aim of this community service activity was to improve the health welfare of the elderly and provide basic health information to the public, especially the elderly regarding blood pressure, blood sugar levels and uric acid, as well as providing education on the results of health examinations carried out so as to realize improvements in the health of the elderly. The method used in carrying out this activity was accidental, namely carrying out health checks on elderly people who come during the activity, then the elderly took turns having their health checked, starting with blood pressure, blood sugar and uric acid. The results of this community service activity showed that of the 24 elderly people, 14 people had hypertension, 12 people had hyperglycemia, and 11 people had hyperuremia. For this reason, it was concluded that the elderly in Aboek Jaloh Village experienced more hypertension (58%), so appropriate follow-up programs were needed to deal with elderly problems, especially degenerative diseases, so that the health of the elderly continued to improve.